The influence of 18Cr10NiTi and ODS 18Cr10NiTi austenitic stainless steels microstructure on the deuterium desorption - Kalchenko, A.S.; Ruzhytskyi, V.V.; Karpov, S.A.; Kolodiy, I.V.; Tikhonovsky, M.A.; Tolstolutskaya, G.D.; Velikodnyi, A.N.; Voyevodin, V.N. (Вопросы атомной науки и техники, 2020)
The thermal desorption spectra of deuterium from 18Cr10NiTi and ODS 18Cr10NiTi steel specimens irradiated with 10 keV D₂⁺ ions were examined. The influence of radiation damage on microstructure and accumulation of deuterium implanted in steels at room temperature and after annealing have been studied. Thermal desorption spectrum (TDS) from a specimen of ODS 18Cr10NiTi steel exhibits deuterium release over a wide temperature range with two well–defined maxima at ~ 420 and ~ 970 K. Two types of precipitates – oxides (Y–Ti–O) and carbides TiC are considered to explain the mechanism of the deuterium trapping to high annealing temperatures.